2008
DOI: 10.1111/j.1467-7717.2008.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Survivor needs or logistical convenience? Factors shaping decisions to deliver relief to earthquake‐affected communities, Pakistan 2005–06

Abstract: In Bureaucratizing the Good Samaritan, Waters (2001) ' (Thomas, 2003, p. 4). This article is an invitation for others to engage in creative humanitarian data management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 8 publications
3
42
0
2
Order By: Relevance
“…The likely root of this situation is the extremely small number of publications describing and analyzing real-life PD-HL operations. Among the handful of publications on the subject, one could list Benini et al (2006);Holguín-Veras et al (2007, 2012a), and Holguín-Veras et al (2014. Holguín-Veras et al (2013) identified intertemporal effects, material convergence, and the impact of the distribution strategy on human suffering as three essential characteristics that must be considered for proper modeling of PD-HL.…”
Section: Basic Literature On Postdisaster Humanitarian Logistics Modementioning
confidence: 98%
“…The likely root of this situation is the extremely small number of publications describing and analyzing real-life PD-HL operations. Among the handful of publications on the subject, one could list Benini et al (2006);Holguín-Veras et al (2007, 2012a), and Holguín-Veras et al (2014. Holguín-Veras et al (2013) identified intertemporal effects, material convergence, and the impact of the distribution strategy on human suffering as three essential characteristics that must be considered for proper modeling of PD-HL.…”
Section: Basic Literature On Postdisaster Humanitarian Logistics Modementioning
confidence: 98%
“…The introduction of technology such as geographic information systems (Benini et al, 2009) or unmanned aerial vehicle systems (Tatham, 2009) have been proposed as ways to enhance the needs assessment process. There has also been an increasing recognition that supply network information management systems have the potential to ease the challenge of managing the subsequent delivery of relief goods (Bartell et al, 2006).…”
Section: Transforming Humanitarian Logisticsmentioning
confidence: 99%
“…address prepositioning of medical supplies using a simulation and develop a model for deciding the size and location of aid distribution facilities for post-hurricane settings. Their model utilizes GIS and spatial optimization technologies to solve p-median and capacitated median type problems.An application of GIS based techniques for needs assessment is provided inBenini et al (2009). The Assessment Capacities Project (ACAPS) is one example dedicated to better deal with the needs assessment operations in the response phase(ACAPS, 2014).…”
mentioning
confidence: 99%